Assessing Integration of Science in Policy-Making Process of the Utilization of Abandoned Lands in Indonesia: Case of Bogor Regency - Purwawangsa, Handian; Nurrochmat, Dodik Ridho; Kartodihardjo, Hariadi; Rustiadi, Ernan (Forestry Faculty, Universitas Hasanuddin, 2022)
Science cannot directly influence policy without a process of knowledge transfer and integration into policy-making called the science-policy interface. On the other hand, not all scientists intend to use their knowledge and findings to influence policy-makers. This condition causes a gap between science and policy. The main objective of this study is to identify various